Risk Factors for Colistin-Resistant Carbapenem-Resistant Klebsiella pneumoniae in the Postacute Care Setting. (2nd September 2022) - Zhang, Helen L; Han, Jennifer H; Lapp, Zena; Snitkin, Evan; Goldstein, Ellie J C; Muldoon, Sean; Tolomeo, Pam; Lautenbach, Ebbing
Abstract: We assessed risk factors for colistin resistance among carbapenem-resistant Klebsiella pneumoniae (CRKP) from 375 patients in long-term acute care hospitals. Recent colistin or polymyxin B exposure was associated with increased odds of colistin resistance (adjusted odds ratio = 1.11 per day of exposure, 95% confidence interval = 1.03–1.19, P = .007). Abstract : Among patients in long-term acute care hospitals with carbapenem-resistant Klebsiella pneumoniae (CRKP) infection or colonization, recent colistin or polymyxin B exposure was associated with increased odds of colistin-resistant CRKP.